Risk of Malignancy Index-3 and Histopathological Diagnosis of Ovarian Mass (Nepal Journal of Obstetrics and Gynaecology, 2020)
Aims: To find out the accuracy of Risk of Malignancy Index (RMI-3) to predict ovarian malignancy pre-operatively.Methods: Intention to treat cross sectional study at Paropakar Maternity and Women’s Hospital in Kathmandu in 2018-2019. Cases with ovarian mass were taken pre-operatively with serum tumor marker (CA-125) and ultrasound report, and histopathology report post- operatively. Pregnancy and diagnosed malignancy were excluded. Sensitivity, specificity, positive and negative predictive values of RMI-3 were calculated at different cut-off values using Receiver operator characteristics (ROC) curve.Results: 36 cases of ovarian tumor from 15 to 60 years (mean=35) were studied. There were 31(86.1%) premenopausal and 5 (13.9%) in menopausal state; 26 (72.2%) were married and 10 (27.8%) unmarried; 19 (52.8%) were multiparous, 9 (25%) were nulliparous and 8 (22.2%) uniparous; 34 (94.4%) presented with pain in lower abdomen; 16 (44.4%) had lump in lower abdomen; 8 (22.2%) had bloody vaginal discharge. Eight out of 36 (22.2%) had malignant histopathology. Taking histopathology to diagnose ovarian malignant tumor RMI 3 score >200 has sensitivity, specificity, positive and negative predictive value of 75%, 92%, 75%, 92% respectively. Taking the cut off value of RMI 3 at >190.5, AUC is 0.906 for ovarian malignant tumor the sensitivity, specificity, positive and negative predictive values were 75%, 93%, 55% and 96% respectively.Conclusions: Risk of Malignancy Index RMI-3 value of 190 or more is the best predictive cut-off to predict ovarian malignancy pre- operatively.Keywords: Cut-off value; ovarian cancer; RMI-3